FORCE MAJEURE DALAM KONTRAK BISNIS AKIBAT PANDEMI CORONA - Jodi Pratama (2021)
The government has issued a number of legal policies, including establishing COVID-19 as a national disaster and large-scale social restrictions. This policy resulted in decreasing economy growth and unfulfilled clause in a contract. The main problem is to prove the parties indicated by force majeure due to the pandemic, and the legal remedies in which unable to fulfill the clause of contract because of force majeure. This research uses juridical normative by tracing applicable regulations and literature related to the problem such as library material. The results shows that the method of proving force majeure must be fulfilled by the elements in articles 1244 and 1245 of the Civil Code which considered force majeure. It is necessary to conduct research and analysis by examining the clauses in the contract and examining the essential elements. Legal remedies of a contract can be carried out in 2 ways, non-litigation and litigation.